Monitoring technologies for CO₂ storage in coal seams and enhanced coalbed methane recovery: A review of field applications - Zhiming Fang; Chenlong Yang; Rundong Wang (Fuel Processing Technology)
CO₂ storage in coal seams coupled with enhanced coalbed methane (CO₂-ECBM) recovery presents a synergistic solution that simultaneously mitigates atmospheric CO2 emissions and enhances hydrocarbon production. This review provides a comprehensive assessment of monitoring technologies employed in global field applications of CO₂-ECBM projects, with particular focus on their deployment across 18 major initiatives in North American, Asian, and European coal basins. We systematically examine monitoring approaches across three critical domains: atmospheric, near-surface, and subsurface. Case studies reveal that while subsurface techniques form the cornerstone for operational monitoring, surface methods prove particularly effective in verifying CO₂ containment integrity. Despite significant technological progress, persistent challenges remain in cost-effective leak detection and long-term prediction of plume migration dynamics. A notable advancement comes from China's pioneering “space-air-ground-well” integrated remote sensing systems, which have substantially improved high-resolution CO₂ migration monitoring. This review emphasizes the necessity of site-specific monitoring protocols that address unique geological constraints-a crucial requirement for ensuring both operational safety and economic feasibility in commercial-scale CO₂-ECBM implementations.